2018
DOI: 10.1215/03616878-4249814
|View full text |Cite
|
Sign up to set email alerts
|

Resource Allocation for Equity in the British National Health Service, 1948–89: An Advocacy Coalition Analysis of the RAWP

Abstract: Britain's National Health Service (NHS) is a universal, single-payer health system in which the central state has been instrumental in ensuring equity. This article investigates why from the 1970s a policy to achieve equal access for equal need was implemented. Despite the founding principle that the NHS should "universalize the best," this was a controversial policy goal, implying substantial redistribution from London and the South and threatening established medical, political, and bureaucratic interests. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Nguyen et al (2014) has mainly considered two elements of CCB: customer feedback and advocacy. The feedback includes solicited and unsolicited information that comes from the customer, and advocacy refers to the recommendation to others that determines other customers (Gorsky and Millward 2018). Yi and Gong (2013) have added another dimension, which helps to assist other customers in meeting their specific requirements based on customers' earlier experiences.…”
Section: Customer Love and Ccbmentioning
confidence: 99%
“…Nguyen et al (2014) has mainly considered two elements of CCB: customer feedback and advocacy. The feedback includes solicited and unsolicited information that comes from the customer, and advocacy refers to the recommendation to others that determines other customers (Gorsky and Millward 2018). Yi and Gong (2013) have added another dimension, which helps to assist other customers in meeting their specific requirements based on customers' earlier experiences.…”
Section: Customer Love and Ccbmentioning
confidence: 99%
“…78 During the late 1980s Coopers and Lybrand were also involved in the review of the Resource Allocation Working Party (RAWP) formula-originally designed in 1976 to try to correct historical imbalances and bring about a more equitable distribution of funding throughout the NHS. 79 The role of management consultants continued to diversify and expand in the health care sphere therefore, and a wider range of firms were beginning to establish an important role at both local and national levels.…”
Section: Governance Efficiency and Trustmentioning
confidence: 99%
“…The survey found that services were 'ad hoc and patchy' with 'no central guidelines and … no resources … made available either centrally or locally' (Prashar and Anionwu 1985, 50). SCD had been left out of the 1975 NHS Resource Allocation Working Party (an attempt to redistribute resources within the NHS) formula (Gorsky and Millward 2018).…”
Section: Representationmentioning
confidence: 99%